Artificial Intelligence Versus Natural Intelligence - Feng Chen (Journal of Dharma, 2024)
Artificial Intelligence (AI) is a relatively recent area of study within philosophy, especially when compared to its long established research in technology. AI gained prominence in the 1950s, initially framed as ‘computer machinery and intelligence’ within the concept of the imitation game, and its influence has only grown over the decades. Today, the philosophy of science has expanded its focus globally, with this book exploring the comparison between artificial and natural intelligence. Roger Penrose and Emanuele Severino engage in a dialogue at a conference, discussing AI as a fascinating topic of the 21st century, particularly in relation to the consciousness of machines and humans. In addition, essays by Ines Testoni, Federico Faggin, Mauro D’Ariano, and Giuseppe Vitiello, along with an introduction by Fabio Scardigli, provide valuable insights into various approaches to the debate. Central to these discussions is the view that consciousness is inherent in actual intelligence. Key questions arise, such as whether consciousness is a central focus of research in technology and science, whether it functions as a mirror—albeit often enigmatic—and the origins of consciousness in animals and humans.